The effect of brewing time on the antioxidant properties and consumer's preference of green tea and jasmine tea - Dwi Hartanti; Alwani Hamad (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2023)
Jasmine tea is a popular tea type obtained from scenting tea (Camellia sinensis (L.) Kuntze) leaves with jasmine (Jasminum sambac (L.) Aiton) flowers. This study aimed to evaluate the antioxidant properties and sensory aspects of jasmine and green tea brewed at different times. The commercial jasmine and green tea were brewed in boiling water at a ratio of 1:100 for 0.5, 1, 2.5, 5, 10, 30, and 60 min. The obtained tea was evaluated for colour, pH, total flavonoid content (TFC), total phenolic content (TPC), 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging activity, and ferric-reducing antioxidant power (FRAP) by standard methods. Thirty-three untrained consumers evaluated the preference for tea from different brewing times. Jasmine tea exerted darker colour, lower pH, higher TFC and TPC, and higher FRAP than green tea. The values of those parameters increased with longer brewing time, with the optimum time being 30 min. However, the longer brewing generated tea liked less by consumers. The most favoured tea was jasmine green tea brewed for 5 min with aroma as the most preferred attribute. Our study suggested that brewing tea for a longer time benefited with better antioxidant properties but disadvantaged in sensory aspects.